1995
DOI: 10.1016/0005-2736(94)00296-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-protein interactions in the purple membrane: structural specificity within the hydrophobic domain

Abstract: In the absence of native-like interactions between bacteriorhodopsin and its neighbouring lipids, the pigment chromophore is reversibly titrated from its purple 570 nm form to a blue-shifted 480 nm form in the moderately alkaline pH range. Quantitation of this acid-base chromophore equilibrium in vesicles prepared from modified lipid mixtures shows that it is absent under conditions where bacteriorhodopsin is allowed to interact with methyl-substituted alkyl chains. The peculiar homogeneous structure of purple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Partial removal of lipids by mild detergent treatment affects photocycle kinetics (29). Wild-type kinetics can be restored by adding back halobacterial lipids, whereas phospholipids lacking the ether-linked dihydrophytanoyl side chains are not effective (100,121), suggesting a specific role for the lipids in maintaining BR functionality.…”
Section: Structural Model and Lipid Interactionsmentioning
confidence: 99%
“…Partial removal of lipids by mild detergent treatment affects photocycle kinetics (29). Wild-type kinetics can be restored by adding back halobacterial lipids, whereas phospholipids lacking the ether-linked dihydrophytanoyl side chains are not effective (100,121), suggesting a specific role for the lipids in maintaining BR functionality.…”
Section: Structural Model and Lipid Interactionsmentioning
confidence: 99%
“…In addition, the well-known hydrogen bond-breaking properties of anesthetics (Sandorfy, 1978) would make them excellent candidates to impair the functionality of the proton pumping channel, but this implies that anesthetics interact close to the chromophore, which does not appear to be the case, as interaction between the retinal and, at least, aromatic neighboring residues are left intact during bR570 transformation into bR480 (Lee et al, 1991). On the other hand, one must not forget that the acid-base-type chromophore equilibration considered here is also i) a property of delipidated (Baribeau and Boucher, 1987) or reconstituted (Lozier et al, 1976;Pomerleau et al, 1995) bacteriorhodopsin; ii) that, when induced with anesthetic or solvents, the phenomenon obeys the lipid solubility rule (Messaoudi et al, 1992) and occurs irrespective of membrane sidedness (Uruga et al, 1991); and iii) that only minor tertiary structural differences have been observed between both spectral forms in the purified state and in anesthetic-treated membranes (Pande et al, 1989;Messaoudi et al 1993). In addition, general anesthetics preferentially locate near the interface and in the hydrocarbon domain of membranes in general (Barber et al, 1995) and of purple membrane in particular (Nakagawa et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This is a strong possibility. Nevertheless, we must keep in mind that bR has strong interactions with its vicinal lipids which can be considered as co-factors [12,23]. Then, the structural unit consisting of the protein with its closely associated lipids, namely the lipid protein interface, could constitute a likely molecular target as well.…”
Section: Discussionmentioning
confidence: 99%